The Easter bunny that overslept - Friedrich, Priscilla (HarperCollins, 2002)
Having slept past Easter, the Easter bunny tries to distribute his eggs on Mother's Day, the Fourth of July, and Halloween, but no one is interested until finally Santa Claus is able to get him back on track.